Deciphering the Mounting Complexity of the p53 Regulatory Network in Correlation to Long Non-Coding RNAs (lncRNAs) in Ovarian Cancer - Sonali Pal; Manoj Garg; Amit Kumar Pandey (Cells, 2020)
Amongst the various gynecological malignancies affecting female health globally, ovarian cancer is one of the predominant and lethal among all. The identification and functional characterization of long non-coding RNAs (lncRNAs) are made possible with the advent of RNA-seq and the advancement of computational logarithm in understanding human disease biology. LncRNAs can interact with deoxyribonucleic acid (DNA), ribonucleic acid (RNA), proteins and their combinations. Moreover, lncRNAs regulate orchestra of diverse functions including chromatin organization and transcriptional and post-transcriptional regulation. LncRNAs have conferred their critical role in key biological processes in human cancer including tumor initiation, proliferation, cell cycle, apoptosis, necroptosis, autophagy, and metastasis. The interwoven function of tumor-suppressor protein p53-linked lncRNAs in the ovarian cancer paradigm is of paramount importance. Several lncRNAs operate as p53 regulators or effectors and modulates a diverse array of functions either by participating in various signaling cascades or via interaction with different proteins. This review highlights the recent progress made in the identification of p53 associated lncRNAs while elucidating their molecular mechanisms behind the altered expression in ovarian cancer tumorigenesis. Moreover, the development of novel clinical and therapeutic strategies for targeting lncRNAs in human cancers harbors great promise.